Biosynthesis of the sesquiterpene germacrene D in Solidago canadensis: 13C and 2H labeling studies - Steliopoulos, P.; Wüst, M.; Adam, K. P.; Mosandl, A.
The biogenetic origin of the isoprenoid building blocks of the sesquiterpene germacrene D was studied in Solidago canadensis. Feeding experiments were carried out with 1-[5,5-D(2)]deoxy-D-xylulose-5-phosphate (D(2)-DOXP), [5-13C]mevalonolactone (13C-MVL)and [1-13C]-D-glucose. The hydrodistillate of a cut shoot fed with D(2)-DOXP was investigated by enantio-MDGC-MS and the volatile fraction of a shoot supplied with 13C-MVL was examined by GC-C-IRMS. The incorporation of [1-13C]-D-glucose was analyzed by quantitative 13C NMR spectroscopy after isolation of germacrene D from the essential oil. Our labeling studies revealed that the biosynthesis of the C-15 skeleton of sesquiterpene germacrene D in Solidago canadensis proceeds predominantly via the methylerythritol phosphate pathway.
Keywords: SOLIDAGO CANADENSIS; ASTERACEAE; BIOSYNTHESIS; METHYLERYTHRITOL PHOSPHATE PATHWAY; SESQUITERPENES; GERMACRENE D; LABELING STUDIES